Phenotypic detection strategies of multidrug-resistant Staphylococcus aureus isolated from cat nasal swab in Madiun city, Indonesia - SAUMI KIREY MILLANNIA; ASWIN RAFIF KHAIRULLAH; MUSTOFA HELMI EFFENDI; SUZANITA UTAMA; SHENDY CANADYA KURNIAWAN; DANIAH ASHRI AFNANI; OTTO SAHAT MARTUA SILAEN; SAFIRA RAMADHANI; SANCAKA CHASYER RAMANDINIANTO; YUSAC KRISTANTO KHODA WARUWU; AGUS WIDODO; GIOVANNI DWI SYAHNI PUTRA; MUHAMMAD THORIQ IHZA FARIZQI; KATTY HENDRIANA PRISCILIA RIWU (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Millannia SK, Khairullah AR, Effendi MH, Utama S, Kurniawan SC, Afnani DA, Silaen OSM, Ramadhani S, Ramandinianto SC, Waruwu YKK, Widodo A, Putra GDS, Farizqi MTI, Riwu KHP. 2023. Phenotypic detection strategies of multidrug-resistant Staphylococcus aureus isolated from cat nasal swab in Madiun city, Indonesia. Biodiversitas 24: 940-946. Over the past ten years, the rise of bacterial disease resistance to antibiotics has presented challenges for veterinarians treating pets. Every day direct contact between pets and their owners is a risk for the spread of harmful bacteria. One of the most frequent patients in veterinary hospitals or clinics is cats. The prevalence of S. aureus infection is rising and becoming more serious as a result of antibiotic resistance, or what is known as multi-drug resistance (MDR). Pet owners and their pets may carry MDR S. aureus through zoonotic transmission. In 2018, MDR events were reported to infect ICU patients at Madiun City Hospital, East Java, Indonesia. Based on this backdrop, the authors decided to perform a study on the S. aureus bacteria resistance test of cefoxitin, tetracycline, erythromycin, gentamicin, and ampicillin bacteria obtained from cat nasal swabs in Madiun City. Making an MSA medium is the first step in bacterial isolation. Then, the Gram stain test identifies the species of Gram bacteria present in the colony. The following step is the catalase and coagulase assays, pinpointing the S. aureus bacterium. The Kirby Bauer disc diffusion method was used to conduct an antibiotic sensitivity test. With the aid of tweezers, paper discs containing the medicines cefoxitin 30 µg, tetracycline 30 µg, erythromycin 15 µg, gentamicin 10 µg and ampicillin 10 µg, are set apart from one another by 25 to 30 mm on an MHA medium. According to sample examination findings, S. aureus was present in 80 (80%), and six isolates (7.5%) were confirmed to be Multi-drug Resistance (MDR). The spread of MDR bacteria in people and animals can result in recurrent infections, a rise in complications, and an increase in morbidity and mortality. Furthermore, rational antibiotic use must be made for both humans and animals to stop the emergence of antibiotic resistance in the veterinary clinic in Madiun City.